[PP.20.06] MONOCYTE COUNTS RELATES WITH SYSTOLIC BLOOD PRESSURE AND PULSE PRESSURE. (September 2017) - Salvado, R.; Agudo-Conde, C.; Recio-Rodriguez, J.; Patino-Alonso, M.; Gomez-Marcos, M.; Laso, A. De Cabo; Salgado, B. Sanchez; Sanchez-Rodriguez, A.; Gonzalez-Sanchez, J.; Garcia-Ortiz, L.
Abstract : Objective: Leucocyte count has been proposed as a marker for predicting cardiovascular risk and appearance of metabolic syndrome. However, few prospective studies have evaluated the relationship between these cells and earlier, subclinical, stages of disease. The aim of this study is to evaluate de relation between monocytes counts and blood pressure (BP). Design and method: We performed a cross-sectional study. We included 396 subjects evaluated in Salamanca for baseline visit of Triple A study. They had a mean age of 57.2 ± 11, 9 years; 57.3% were women. Measurements: habits and medication, anthropometric measurements, systolic and diastolic BP, pulse pressure (PP), mean BP, fasting glucose, glycosylated haemoglobin, lipid profile and white blood cell counts. Participants were categorized by monocyte count terciles. Results: The mean absolute monocyte count was 0.50 ± 0.17 x 109/L. In this population 249 (62.9%) had hypertension The mean blood pressure values were: systolic BP 127.5 ± 18.8 mmHg; diastolic BP 78.2 ± 11.1 mmHg; mean BP 94.6 ± 12.3 mmHg; PP 49.3 ± 14.7 mmHg. The mean values of this variables are more elevated in higher monocytes counts (when divided in terciles). In linear multiple regression, monocytes maintain a positive association with systolic BP (beta = 13.8, CI 95% 5.5–22.1) and PP (beta = 15.7, CI 95% 8.3–2) when adjusted for age, sex, dyslipidaemia, diabetes mellitus type 2, smoking, obesity, hypertension, and medication: antihypertensive, antidiabetic, and lipid lowering drugs. Conclusions: Monocyte count have a positive association with systolic blood pressure and pulse pressure values, independently of cardiovascular risk factors and medication.